Perancangan Program Stimulasi Motorik Halus Pada Anak Usia 1 – 2 Tahun - Eka Sufartianinsih Jafar; Nurul Ilma; Wilda Ansar; Irdianti; Nurfajriyanti Rasyid (BULLET : Jurnal Multidisiplin Ilmu, 2023)
Early childhood is a very important period of development because it can affect the next period of child development. Therefore, it is important for parents or caregivers to provide stimulation to children. Stimulation of children's abilities can support dan optimizing their development. This stimulation includes various aspects of development, one of which is fine motor aspects. The results of observations and interviews at X Instantion found that stimulation is still needed for children aged two years and there is a lack of appropriate stimulation tools for children aged 18-24 months. This research aims to make stimulation tools specifically for children aged 2 years by utilizing used goods. The research is carried out in two stages and uses observation techniques to measure children's abilities. In the application of stimulation tools, children show interest and are able to follow the instructions. The results of the observation found that there’s a changes in fine motor skills of children who participated in the whole activities. This change icluded progress the child's level of independence and success in using the stimulation tools.